Optimizing suitable solvent for phenylpropanoid extraction and antioxidant activities in Agastache rugosa hairy roots - Nguyen, Bao Van; Lim, Jinsu; Kim, Kihyun; Seo, Hyewon; Sathasivam, Ramaraj; Park, Jong Seok; Kim, Jae Kwang; Park, Sang Un (Journal of Phytology, 2024)
Agrobacterium-mediated hairy roots (HRs) can induce genetic stability, rapid growth, and the synthesis of bioactive compounds in plant roots. Agastache rugosa is otherwise called Korea Mint and several studies have reported that this plant has been used for the treatment of various diseases due to the presence of a variety of bioactive compounds. A. rugosa HRs are rich in secondary metabolites than the seedling roots, and the HRs extract might be more useful in pharmacology, especially in cosmetology. This study aimed to select the suitable solvent for the extraction of phenylpropanoid compounds, total phenolic (TP), flavonoid (TF), and antioxidant activities (DPPH, ABTS scavenging activity, and reducing power assay). In this study, we extracted the A. rugosa HRs with three different extracts of solvent (water, MeOH, and EtOH) of A. rugosa HRs and analyzed the phenylpropanoid compounds, TP, TF, and antioxidant activities. The result showed that 70% MeOH extracts showed the highest activities in all assays, followed by the 70% EtOH, and water extracts. In addition, 70% of MeOH extracts showed the highest TP and TF (46.14±0.25 GAE mg/g DW and 65.46±1.41 QE mg/g DW, respectively) contents, which was 1.96- and 1.76- times higher than that of the water extracts. The phenylpropanoids in A. rugosa HR extracts were identified by using HPLC, and the results showed that 70% MeOH and EtOH showed the highest contents. Regarding these results, we can conclude that 70% MeOH is the optimal solvent to extract the A. rugosa HRs for the highest phenylpropanoid, TP, TF content, and antioxidant activities. This study might be useful for producing useful compounds at an industrial scale.